EXTRACTION OPTIMIZATION PROPOLIS IN THE FUNCTIONAL DRINK OF KEPROK BATU 55 ORANGE ( Citrus reticulate Blanco) - Rizka Ayu Rifdah Ifrada; Erryana Martati; Teti Estiasih (Jurnal Pangan dan Agroindustri, 2022)
Propolis has been used in various traditional medicines throughout the world and has been shown to have anti-inflammatory activity due to its flavonoid and CAPE content. Naringenin on Tangerines Stone 55 ( Citrus reticulata Blanco ) is a flavonoid glycoside that has the potential as an anti-inflammatory and immunomodulator . Functional drinks from these 2 ingredients can be an anti-inflammatory treatment. By using Maceration Extraction, extraction was carried out with variations in the ratio of water and propolis of 1:5, 1:10 and 1:15 within 15 minutes, 30 minutes and 45 minutes at 50 o C, 60 o C and 70 o C. Conditions optimum extraction with the highest phenolic content ( 4.88 mg GAE/g ) at 30 °C, for 45.00 minutes, and the water:propolis ratio was 1:5. While the total flavonoids were highest at the water:propolis ratio 1:5 for 30 minutes at 50°C (0 . 46 mg QE/g).